Pericentric inversion events in karyotypic distinction of Brazilian lizards of genus Phyllopezus (Squamata, Gekkonidae) detected by chromosomal banding patterns - Pellegrino, KCM; Kasahara, S.; Rodrigues, M. T.; Yonenaga-Yassuda, Y. (Wiley-Blackwell, 1997)
Cytogenetic investigations based on conventional and differential staining analysis (C-and replication R-banding and Ag-staining) were carried out on eight specimens of Phyllopezus periosus, 17 of P. pollicaris pollicaris, and one of P. pollicaris przewalskii collected from different localities of Brazil. P. periosus and P. p. pollicaris share the same diploid number of 2n = 40 chromosomes, and their karyotypes are very distinctive regarding to the number of biarmed and uniarmed chromosomes. After careful side-by-side comparison of R-banded chromosomes in both taxa, pronounced homology between, at least, eight pairs was revealed. The R-banding patterns allowed us to postulate that karyotype differentiation could be due to pericentric inversion events. P. p. przewalskii (2n = 38) exhibited a very similar karyotype to that found in P. p. pollicaris, except for the presence of one metacentric pair, which probably resulted from a Robertsonian rearrangement. Single and multiple pairs of NOR-bearing chromosomes, showing variation in number and location, were detected among the three forms of Phyllopezus. Similar C-banding patterns were found in P. periosus and P. p. pollicaris. Sex chromosomes were not positively identified.